Validity and test-retest reliability of a kinesthetic perception test for blind people - Hendrig Joko Prasetyo; Sapta Kunta Purnama; Rumi Iqbal Doewes; Rony Syaifullah Sugiyanto (Universidad de Murcia, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.